(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
This article analyzes a collection of lyrical works by Alisher Navoi. The genres of poetry related to the motto "Khazoyin ul-maoni" are defined. The themes and poetics of genres are highlighted. Poems are classified by structure and content. The artistic pictorial means used in the poems are revealed. According to the structure of the verses, there are types.